In Vitro Fertilization of Immature Oocytes by Testicular Sperm: Animal Model for Azoospermic Infertile Patients - Alanssari, Saeeda A. M.; Kjelland, Jie. Liu, Mike; Albananchi, M. Ridha-; Kraemer, Duane C. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Men with azoospermia require testicular and epididymal sperm aspiration for intracytoplasmic sperm injection. Women over 37 years of age demonstrate an increase number of immature oocytes after induction of ovulation. The development of a technique for in vitro maturation (IVM) and fertilization (IVF) of the oocytes using testicular, epididymal and vassal sperm (TS, ES, VS, respectively) will be of therapeutic value for the treatment of azoospermic patients. Objectives: The goal of the study was to develop an animal model for the treatment of infertile couples with obstructive azoospermia and immature oocytes. Materials and Methods: Canine ovaries and testes were collected from a local animal clinic. Immature oocytes were retrieved from the ovaries and cultured in modified tissue culture medium (MTCM). The mature oocytes were in vitro fertilized by TS, ES, and VS. The normality of the fertilized oocytes was studied. Results: Sperm motility index was significantly higher (P<0.01) in sperm retrieved from the vas deference compared to ES and TS. The concentration of the sperm was significantly higher (P<0.05) in the testes compared to epididymis and vas deference while VS and ES normal morphology were significantly (p<0.01) better than TS. Viable oocyte percentage was significantly higher (P<O.05) in 72 hours versus 96 hours culture durations. Significant higher IVF was reported in VS compared to other groups (P < 0.05) and the SPI was significantly higher after 96 versus 72 hours duration (P<O.05). Conclusion: IVM of the oocytes in MTCM for 72 and 96 h resulted in a significant increase in IVM rate compared to 48,120, and 144 h durations. In vitro viable mature oocytes showed higher IVF rates when fertilized with VS compared to ES and TS. The results showed that canine oocytes are good model for azoospermic patients.